Preparation and properties of a Jauman type microwave absorbing ceramic with carbon felt film. Issue 1 (1st January 2021) - Li, Xiangming; Yang, Qing; Zhou, Guangyou; Zhu, Xiaotao; Ren, Guina; Zhang, Wei; Yang, Meiling; Gao, Zhen
Abstract: A Jauman type microwave absorbing ceramic was prepared by adding carbon felt film in a ceramic matrix from the mixture of quartz, calcium sulphate, talc and sodium tetraborate. The sintering temperature and the addition of carbon felt film have a great impact on the properties of the ceramics. The ceramics prepared by sintering at 780 °C show the highest flexural strength due to the suitable fibre/matrix bonding strength. The ceramics with two layers of carbon felt film have much better microwave absorbing performance than those with one layer of carbon felt film, and the microwave absorbing performance of the ceramics could be better improved by using a conductive semi−transparent thin film as the loss layer. The ceramic containing two layers of carbon felt film with mass per unit area of 10 g/m 2 is a good structural absorbing material possessing high flexural strength, uniform microstructure, good temperature resistance and excellent microwave absorbing performance with the whole reflectivity–versus–frequency curve below −10 dB and mean reflectivity of −11.3 dB in the frequency ranging from 8.0 to 18.0 GHz.